Land of the eagle : a natural history of North America - Peck, Robert McCracken, 1952- (New York : Summit Books, 1990)
Examines the different attitudes of the settlers and the Native Americans and discusses how they helped shape the North American continent.
Includes bibliographical references (p. 275-282) and index.
Booklist.
Library Journal.
School Library Journal.
Young Adult.
Young Adult
Keywords: Natural history -- North America; Natural history -- North America -- Pictorial works; Natural history -- North America